Gastronomy Tourism and Food Security: Somatic, Auditory, Visual, Intellectual Approaches in Cireundeu Indigenous Village - Panji Yudha Uttama; Awaludin Nugraha; Evi Novianti (GoAcademica Research & Publishing, 2026)
This study addressed the need to transform conventional gastronomy tourism into an educational medium for environmental resilience. The research aimed to explore how gastronomy tourism in the Cireundeu Indigenous Village internalized local food security values for tourists through a somatic, auditory, visual, and intellectual learning approach. Utilizing a qualitative method with an interactive data analysis framework, the study collected data through participant observation and in-depth interviews. Informants were selected using a purposive sampling technique, involving the traditional leader, community figures, and women’s group representatives. The results demonstrated that the indigenous community's philosophy regarding the historical transition from rice to cassava was successfully transformed into a holistic educational experience. The research mapped thirteen cultural expressions into four learning dimensions. Tourists experienced physical involvement through cassava processing, absorbed historical narratives, observed traditional rituals, and constructed an understanding of food sovereignty. In conclusion, the somatic, auditory, visual, and intellectual approach effectively deepened tourists' understanding of food diversification and environmental sustainability.